Sweet tomorrows - Macomber, Debbie (New York Ballantine Books, 2016)
The conclusion to the "Rose Harbor series, set in the picturesque town of Cedar Cove, Sweet Tomorrows is a vibrant and poignant novel of letting go of fear, following your heart, and embracing the future--come what may."--
112067
Keywords: Hotelkeepers -- Fiction; Female friendship -- Fiction; Interpersonal relations; Romance -- Contemporary; Contemporary Women; Love stories; Romance fiction; Fiction; Love stories